Changes in compatibility, tack and viscoelastic properties of ethylene n-butyl acrylate (EBA) copolymer–pentaerythritol rosin ester blend by adding microcrystalline wax, Fischer–Tropsch wax and mixture of waxes. (March 2016) - Moyano, María Alejandra; París, Rodrigo; Martín-Martínez, José Miguel
Abstract: Ethylene n-butyl acrylate copolymer (EBA) instead of ethylene vinyl acetate copolymer (EVA) can be used as the base polymer for hot melts. The lower polarity of EBA should affect differently the compatibility with the wax and the tackifier as compared to EVA. In this study the compatibility, tack and viscoelastic properties of EBA copolymer–pentaerythritol rosin ester blended with waxes of different nature (Fischer–Tropsch and microcrystalline) and in different amounts were studied. An increase in compatibility of EBA-copolymer blend with microcrystalline wax was produced leading to increased tack and open time, and reduced viscosity. In contrast, the addition of Fischer–Tropsch wax decreased the compatibility and tack of the EBA-copolymer blend. The addition of a mixture of microcrystalline and Fischer–Tropsch wax caused a better balance in the rheological properties and thermal stability of the EBA-copolymer blends. Finally, an increase in the wax mixture content produced a complete removal of tack caused by dilution of the tackifier in the polymer blend rather than by differences in compatibility.